2020
DOI: 10.1097/pas.0000000000001633
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 Expression in Endocervical Adenocarcinoma

Abstract: Programmed death-1 ligand (PD-L1) expression has been used as a predictive marker for response to immune checkpoint inhibitors and has been reported to have prognostic value. Its prevalence and significance in endocervical adenocarcinoma (ECA) remain underinvestigated. We evaluated PD-L1 expression and CD8+ tumor-infiltrating lymphocyte density in whole tissue sections of 89 ECAs. PD-L1 expression was observed in 68% of ECAs by combined positive score (CPS, cutoff 1) and 29% of ECAs by tumor proportion score (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…As one of the most important immune checkpoints, several studies have investigated PD-L1 prevalence in cervical cancers. 21,[55][56][57][58][59][60][61][62][63][64] Studies have demonstrated a significant correlation between HPV infection and increased PD-L1 expression in cervical SCC and cervical intraepithelial neoplasia. 60,61,63,65 Although the underlying mechanism is not fully understood, those studies suggested impaired immune surveillance by the upregulated PD-L1 expression caused by HPV infection plays a crucial role in the SCC/cervical intraepithelial neoplasia development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As one of the most important immune checkpoints, several studies have investigated PD-L1 prevalence in cervical cancers. 21,[55][56][57][58][59][60][61][62][63][64] Studies have demonstrated a significant correlation between HPV infection and increased PD-L1 expression in cervical SCC and cervical intraepithelial neoplasia. 60,61,63,65 Although the underlying mechanism is not fully understood, those studies suggested impaired immune surveillance by the upregulated PD-L1 expression caused by HPV infection plays a crucial role in the SCC/cervical intraepithelial neoplasia development.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, a study by Rivera-Colon et al 21 suggested that PD-L1 may be an unfavorable prognostic marker for ECAs. Similar to that study, our data demonstrated a high prevalence of PD-L1 in usual-type HPVA ECAs (25% by TPS and 55% by CPS).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, heterogenous intratumoral PD‐L1 expression is frequently observed in ECA, which could impact the effectiveness of PD‐L1‐directed immunotherapy in these cancers. Moreover, PD‐L1 expression in ECA patterns B and C was significantly increased compared to other patterns 13 . It was also found that gastric adenocarcinoma (GEA) tumors expressing PD‐L1 have worse outcomes than GEA tumors that do not expression PD‐L1 14 .…”
Section: Introductionmentioning
confidence: 95%
“…Moreover, PD-L1 expression in ECA patterns B and C was significantly increased compared to other patterns. 13 It was also found that gastric adenocarcinoma (GEA) tumors expressing PD-L1 have worse outcomes than GEA tumors that do not expression PD-L1. 14 In addition, TILs play an important role in the development of cervical cancer.…”
Section: Introductionmentioning
confidence: 99%